Trends in fetal monitoring through phonocardiography: Challenges and future directions. (March 2017) - Chetlur Adithya, Prashanth; Sankar, Ravi; Moreno, Wilfrido Alejandro; Hart, Stuart
Highlights: Current Standards of Fetal Monitoring, Fetal Phonocardiogram Signal Composition and its Diagnostic Value. Survey of Data Acquisition Approaches, Data Acquisition Systems, Databases and Existing Commercial Products. Current Trends and Feasibility of Data Analysis, Processing and Classification Algorithms. Review of Existing Mathematical Models for Synthetic Data Generation. Challenges and Potential Future Directions in Data Collection, Analysis and Processing and Modelling. Abstract: Monitoring the well-being of a fetus through Fetal Phonocardiography (FPCG) has been occurring for more than a century. Throughout history, there have been continuous advances in sensor development, data acquisition systems, and signal processing techniques. Despite these advancements, FPCG based point of care technologies are facing serious challenges in translating from basic research to clinical trials and commercialization. This is partly due to the noisy characteristic associated with FPCG, to the lesser clinical knowledge about fetal and maternal physiological profiles, to the unavailability of gold standard databases, and to the limited application of reliable signal processing techniques. In order to understand why FPCG continues to be underutilized, it is necessary to know about the existing standards of fetal monitoring, data collection trends, and the signal processing aspects. To serve this purpose, this paper will first provide an overview of the existing standards of fetal monitoring and then provide a comprehensive survey on Fetal Phonocardiography with focus on trends in data collection, signal processing techniques and synthesis models that have been developed to date. Finally, a set of guidelines will be proposed for future research and use in signal analysis, processing and modeling based on the outlined challenges.